Mammal and herpetofauna diversity and activity patterns in the Lumbini Crane Sanctuary, Nepal - Banjade, Baburam; Bhuju, Ukesh Raj; Suwal, Rajendra Narsingh; Awasthi, Balram (Nepal Journal of Environmental Science, 2024)
The Lumbini Crane Sanctuary (LCS) within the New Lumbini Village located in the north block of the Lumbini Master Plan Area (LMPA) under the jurisdiction of the Lumbini Development Trust (LDT), is a vital ecological site harboring diverse mammal and herpetofauna species. This study, conducted in the Lumbini Crane Sanctuary during September and October 2022, documented mammals, reptiles, and amphibians, and analyzed mammal activity patterns in relation to human and livestock activity. The study documented 16 mammalian species and 12 herpetofaunal species (8 reptiles and 4 amphibians), utilizing both direct methods, such as camera traps, and line transects and indirect approaches such as sign surveys and key informant interviews. Five mammal species- Blue Bull (Boselaphus tragocamelus), Golden Jackal (Canis aureus), Indian Hare (Lepus nigricollis), Indian Grey Mongoose (Herpestes edwardsi), and Wild Boar (Sus scrofa) exhibited distinct activity patterns. The Blue Bull displayed consistent daytime activity, peaking in the late afternoon, while the Golden Jackal and Wild Boar showed bimodal patterns, avoiding peak human activity hours. The Indian Hare and Wild Boar were most active in the early morning when human and livestock presence was minimum. These activity patterns suggest possible behavioral adaptations to human pressures, highlighting conservation challenges such as habitat destruction, pollution, and impacts from feral livestock in the area. Promoting sustainable tourism is crucial and future research should prioritize long-term studies to better understand the biodiversity and behavior of mammals and herpetofauna in the Lumbini Crane Sanctuary.